STRUKTUR MODAL PENDEKATAN DINAMIS PERUSAHAAN OTOMOTIF DAN KOMPONENNYA SAAT KRISIS GLOBAL 2008 - Dewi, Syanti; Ramli, Ishak (Jurnal Ekonomi, 2016)
The increase in business during the global crisis to the challenge of funding and capital structure dynamic analysis approach is suitable for the observation of the capital structure. This study is intended to demonstrate the influence of profitability, firm size, cost of equity, debt cost, and firm value volatility, leverage and speed adjustment sertaoptimal the capital structure. By using the auto company's financial statements and its components in a data 2008-2012 profitability, firm size, cost of equity, debt cost, danfirm value volatility analyzed using multiple regression analysis to examine the effect on the capital structure and leverage optimal data and speed adjustmentdianalisis method Generalized Moment Method (GMM) to examine the achievement of optimal capital structure and speed of achievement of optimal capital structure. The results found that the only significant profitability and firm size negatively affects the capital structure, the cost is being equity, debt cost, and firm value volatilitytidak significantly affect their capital structure. The automotive industry and its components was successfully adjust its capital structure to an optimal position, but the adjustment is slow. In a global crisis of capital structure adjustment to the optimal capital structure is progressing slowly in view of the difficulty of finding external funding sources.